Lara the black cat fairy - Meadows, Daisy (Meadows, Daisy. Magical animal fairies, 2012)
Rachel and Kirsty are going to an outdoor adventure camp, but Jack Frost has stolen the seven magical animals from their fairies and they must rush to help Lara the Black Cat Fairy save her black cat, Lucky, from the goblins after her lucky escape.